(untitled) (Research, Society and Development, 2021)
Prenatal care performed by nurses is important for the prevention or early detection of pathological changes, thus providing a healthy pregnancy and a good development of the fetus. Objective: The study aimed to know, understand and verify how to provide prenatal care provided by nurses in primary care. Methodology: This is an integrative narrative literature review, which sought scientific publications from 2014 to 2021, on the online platforms BVS, ScIELO BRASIL and GOOGLE ACADÊMICO. Using the following key words: “Pregnancy”, “Prenatal”, “Nurse assistance”. Used the terms: “Prenatal”, “nurse assistance”. Results: The results found were that prenatal care welcomes the woman from the beginning of pregnancy, ensuring at the end of pregnancy, the birth of a healthy child and the guarantee of maternal and neonatal well-being, promoting health and identifying, early onset of anomalies, and reducing neonatal mortality. Final considerations: The gestational and puerperal process brings changes to the woman’s body, both physiologically and emotionally, in addition to the change in the family’s routine. The professional nurse who accompanies this pregnant woman, from the prenatal period, can act to reduce abnormalities that may interfere with the gestational process.